Charles Taylor and the Place of the Transcendent in Secular Modern Lives - Campbell, Anthony Edward Hugh (Université Saint-Paul / Saint Paul University, 2017)
This study explores the thought of Charles Taylor, Canada's preeminent living philosopher, concerning "our present predicament." This, he defines as the unprecedented freedom but also unavoidable need we moderns have in a secular modern world to chose between belief and unbelief in our individual lives. It is a choice we must make, but it entails very high stakes. Appropriating Hegel's dialectical perspective, Taylor sees it as a choice between enjoying "flourishing" lives with possibly some degree of "fullness" in the immanent frame, or aspiring to flourishing lives with the possibility of the fullest of fullness of life living in a horizon of the transcendent. The risk in the atheistic exclusive humanist and anti-humanist frames is the threat described by Nietzsche of nihilism, decadence, violence and suppression. Taylor warns about the risks but is a "booster" of secular modernity because of its undeniable benefits to humanity. Moreover, he agrees with Hegel's "spiral" view as opposed to opposing linear and deterministic views of historical development. Therefore, he anticipates a reconciliation of contemporary "contradictions" in modern culture in the form of individual personal transformation towards a new "agapiac" transcendent synthesis. This hopeful message sees a recovery of spiritual "goods" and personal "articulacy" from the richness of the past without the futile expectation of a return to that past. This would open the possibility of a new place for the fullness of the transcendent in secular modern lives.
Keywords: Charles Taylor; secular; secularity debate; fullness; flourishing; dialectic; Hegel; Nietzsche; transcendent horizon; immanent frame; synthesis; reconciliation; transformation; agape